1988
DOI: 10.1111/j.1365-2133.1988.tb03204.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of psoriasis by a topical vitamin D3 analogue (MC 903) in a double-blind study

Abstract: The effect of the non-calciotropic vitamin D3 analogue MC 903 on psoriasis vulgaris was assessed in a double-blind, placebo controlled trial in 30 patients. Lesions on one side of the body were treated for 6 weeks with a cream containing 10 figig, 33 /^g/g or 100 figig MC 903 and lesions on the other side were treated with the cream base alone, according to a randomized design. Nine of the 10 patients in each treatment group completed the study. MC 903 cream gave a statistically significant decrease in erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(93 citation statements)
references
References 19 publications
0
91
0
2
Order By: Relevance
“…A beneficial effect of the combination of calcipotriol and phototherapy was first shown by Kragballe et al [5], comparing calcipotriol alone with calcipotriol + UVB in a right-left-side study design. The difference in favour of the combination as compared with calcipotriol alone was, however, not significant, probably due to the low number of patients (20 patients) studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A beneficial effect of the combination of calcipotriol and phototherapy was first shown by Kragballe et al [5], comparing calcipotriol alone with calcipotriol + UVB in a right-left-side study design. The difference in favour of the combination as compared with calcipotriol alone was, however, not significant, probably due to the low number of patients (20 patients) studied.…”
Section: Discussionmentioning
confidence: 99%
“…epidermal hyperproliferation, epidermal cell differentiation and cutaneous inflammation [2, 3, 4]. Clinical experience with calcipotriol has shown its efficacy in the treatment of psoriasis [5, 6]. A previous study indicated that the effect of calcipotriol in psoriasis was improved by the addition of UVB [7].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical stainings have shown that corticosteroids reduce both the epidermal hyperproliferation and the dermal inflammatory infiltrate, both effects being detectable within 2–3 weeks [12, 13], whereas the expression of keratin 10 (terminal differentiation) is unchanged [12]. Vitamin D 3 analogues result in a decreased epidermal proliferation, increased epidermal differentiation and a decreased dermal inflammatory infiltrate [14, 15]. For vitamin D analogues, it takes about 6–8 weeks before the effect on dermal lymphocyte infiltration can be detected, and it has been suggested that vitamin D 3 analogues are less effective in reducing the number of inflammatory cells than in modifying keratinocyte proliferation and differentiation [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Ennek magyarázata lehet, hogy az aktív Dvitamin gyorsítja a keratocyták differenciálódá sát és gátolja a proliferációjukat [47,48,49], ugyan akkor előnyösen hat a betegség kialakulásában szerepet játszó immunfolyamatokra is [50]. Napjainkban a be tegség egyik alapkezelése az ideális Dvitaminszint biztosítása mellett alkalmazott kalcitriol vagy a kevéssé hypercalcaemizáló Dvitaminanalógok (kalcipotriol, ta kalcitol, maxakalcitol) lokális használata [51,52,53,54,55,56,57].…”
Section: D-vitamin-hiány Hatása a Bőrre Dr Wikonkál Norbertunclassified